PENINGKATAN AKTIVITAS BELAJAR MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN IPAS MATERI KERAGAMAN BUDAYA KELAS IV DI SDN MAYANGCINDE - Yulyanti, Lia; Nugraha, Fajar; Mahendra, Hatma Heris (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2025)
The transformation of the Merdeka Curriculum requires the implementation of learning that maximizes student engagement, particularly in the subject of Natural and Social Sciences (IPAS). The low level of student engagement has become a fundamental issue that hinders the achievement of IPAS learning objectives in the topic of cultural diversity. This study aims to examine the improvement of student learning activities through the application of the Problem-Based Learning (PBL) model in Grade IV at SDN Mayangcinde. The research method used is Classroom Action Research based on the Kemmis and McTaggart model, with 12 fourth-grade students as the subjects. The implementation was carried out in two learning cycles consisting of the stages of planning, implementation, observation, and reflection. Data were collected using student learning activity observation sheets and analyzed using percentage achievement categories: very good (70–100%), good (55–69%), fair (40–54%), and poor (0–39%). The results showed a significant increase in student engagement, from 33.33% in the pre-action stage to 58.33% in cycle I and reaching 83.33% in cycle II. The PBL model proved effective in enhancing student participation through real problem-solving, collaborative learning, and independent knowledge construction. The implementation of the PBL model can improve student learning activities in the IPAS subject, specifically in the topic of cultural diversity, in Grade IV at SDN Mayangcinde. ABSTRAKTransformasi Kurikulum Merdeka menuntut penerapan pembelajaran yang memaksimalkan keterlibatan belajar siswa, khususnya pada mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS). Rendahnya keterlibatan belajar siswa menjadi masalah mendasar yang menghambat tercapainya tujuan pembelajaran IPAS pada materi keragaman budaya. Penelitian ini bertujuan untuk mengkaji peningkatan aktivitas belajar siswa menggunakan model pembelajaran  Problem Based Learning (PBL) kelas IV SDN Mayangcinde. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas model Kemmis dan McTaggart dengan subjek penelitian 12 siswa kelas IV. Penerapan dilakukan melalui dua siklus pembelajaran dengan tahapan perencanaan, pelaksanaan, observasi, dan refleksi. Data dikumpulkan menggunakan lembar observasi aktivitas belajar siswa dengan analisis persentase capaian berkategori sangat baik (70-100%), baik (55-69%), cukup (40-54%), dan kurang (0-39%). Hasil penelitian memperlihatkan adanya peningkatan keterlibatan belajar yang signifikan dari pratindakan 33,33% menjadi 58,33% pada siklus I dan mencapai 83,33% pada siklus II. Model PBL terbukti efektif dalam mengaktifkan partisipasi siswa melalui pemecahan masalah nyata, pembelajaran kolaboratif, dan pembentukan pengetahuan mandiri. Penerapan model PBL dapat meningkatkan aktivitas belajar siswa dalam mata pelajaran IPAS, materi keragaman budaya kelas IV SDN Mayangcinde.